2015
DOI: 10.1039/c5nj02252e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of o-fluorosulfinylaniline. A comparative vibrational study of fluorinated sulfinylaniline series

Abstract: ARTICLE This journal isThe synthesis of o-fluorosulfinylaniline is reported with the aim to complete the fluorinated sulfinylanilines series. The FT-IR and Raman spectra of o-fluorosulfinylaniline are recorded and the fundamental modes of its vibrational frequencies are assigned together with a tentative assignment of the NMR and mass spectra. Quantum chemical calculations on the optimized geometry predict in the liquid phase a planar structure with syn orientation of the -N=S=O moiety (syn of the S=O double b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As it was reported previously [2 , 34-37] N = S and S = O stretching modes are strongly coupled therefore, these vibrations may be better described as antisymmetric and symmetric stretching modes of the sulfinyl group. The series of compounds studied by our research group showed that for halogen monosubstituted sulfinylaniline derivatives (X = F [12][13][14] and Cl [15 , 16] ), the characteristic stretching modes of the NSO group change in a larger or smaller degree according to the position of the substituent in the aromatic ring. Not only frequency values modify according to the position of the substituent, but they also change in response to the electronic density in the aromatic ring itself.…”
Section: Vibrational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As it was reported previously [2 , 34-37] N = S and S = O stretching modes are strongly coupled therefore, these vibrations may be better described as antisymmetric and symmetric stretching modes of the sulfinyl group. The series of compounds studied by our research group showed that for halogen monosubstituted sulfinylaniline derivatives (X = F [12][13][14] and Cl [15 , 16] ), the characteristic stretching modes of the NSO group change in a larger or smaller degree according to the position of the substituent in the aromatic ring. Not only frequency values modify according to the position of the substituent, but they also change in response to the electronic density in the aromatic ring itself.…”
Section: Vibrational Analysismentioning
confidence: 99%
“…Fluoro-substituted compounds were reported as relevant starting materials with great potential in the pharmaceutical industry [9][10][11] . Our recent studies regarding the conformational and vibrational properties of a series of fluorine [12][13][14] and chlorine [15 , 16] monosubstituted Nsulfinylanilines proved that the properties vary according to the position of the substituent in the aromatic ring and the prevalence of different electronic effects. These halogen atoms interact through mesomeric ( + M) and inductive (-I) effects with different extents.…”
Section: Introductionmentioning
confidence: 99%
“…Our code, QUMVIA, uses analytic expressions for the VSCF integrals in a distributed Gaussian (DG) basis set…”
Section: Theorymentioning
confidence: 99%